2019
DOI: 10.2147/ijn.s208089
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regulating intracellular ROS signal by a dual pH/reducing-responsive nanogels system promotes tumor cell apoptosis</p>

Abstract: Purpose: The levels of reactive oxygen species (ROS) in tumor cells are much higher than that in normal cells, and rise rapidly under the influence of exogenous or endogenous inducing factors, eventually leading to the apoptosis of tumor cells. Therefore, this study prepared a dual pH/reducing-responsive poly ( N -isopropylacrylamide-co-Cinnamaldehyde-co-D-α-tocopheryl polyethylene glycol 1000 succinate, P ss NCT) nanogels, which employed two exogenous R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…The ROS detection tests employed the DCFH-DA as the ROS marker to evaluate the ROS generation in MCF-7 cells induced by different CA or DOX preparations, which is hydrolyzed to DCF and generate highly green fluorescent signal once reacted with the intracellular ROS. 39 From Figure 10A and B , the intracellular ROS levels increased significantly after incubated by different CA preparations. The ROS levels of different experimental groups were 3.50 (MSN CA @GO DOX -HA), 3.26 (MSN CA @GO DOX ), 2.08 (MSN CA ), and 2.20 (CA) times of the blank control group, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The ROS detection tests employed the DCFH-DA as the ROS marker to evaluate the ROS generation in MCF-7 cells induced by different CA or DOX preparations, which is hydrolyzed to DCF and generate highly green fluorescent signal once reacted with the intracellular ROS. 39 From Figure 10A and B , the intracellular ROS levels increased significantly after incubated by different CA preparations. The ROS levels of different experimental groups were 3.50 (MSN CA @GO DOX -HA), 3.26 (MSN CA @GO DOX ), 2.08 (MSN CA ), and 2.20 (CA) times of the blank control group, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, STAT3 overexpression almost completely abolished the ROS accumulation induced by galangin treatment, indicating galangin induced ROS generation through STAT3 suppression. Many researches have proved that ROS enhanced cell apoptosis ( Cui et al, 2018 ; Dong et al, 2019 ), however, it has not been found that STAT3 also modulates ROS levels. Our results demonstrated that STAT3 activation inhibited ROS overload.…”
Section: Discussionmentioning
confidence: 99%
“…High metabolic levels are a hallmark of tumor progression, including myeloma progression. 40 Excess mitophagy induced by HHT decreases the number and percentage of mitochondria, 41 which accelerates MM cell death due to the lack of energy metabolism (Figure 6). Taken together, HHT submit your manuscript | www.dovepress.com…”
Section: Discussionmentioning
confidence: 99%